Predicting Venous Thromboembolic Events in Patients with Coronavirus Disease 2019 Requiring Hospitalization: an Observational Retrospective Study by the COVIDIC Initiative in a Swiss University Hospital. (10th November 2020) - Kampouri, Eleftheria; Filippidis, Paraskevas; Viala, Benjamin; Méan, Marie; Pantet, Olivier; Desgranges, Florian; Tschopp, Jonathan; Regina, Jean; Karachalias, Eleftherios; Bianchi, Christophe; Zermatten, Maxime G.; Jaton, Katia; et al.
Abstract : Background . Coronavirus disease 2019 (COVID-19) can result in profound changes in blood coagulation. The aim of the study was to determine the incidence and predictors of venous thromboembolic events (VTE) among patients with COVID-19 requiring hospital admission. Subjects and Methods . We performed a retrospective study at the Lausanne University Hospital with patients admitted because of COVID-19 from February 28 to April 30, 2020. Results . Among 443 patients with COVID-19, VTE was diagnosed in 41 patients (9.3%; 27 pulmonary embolisms, 12 deep vein thrombosis, one pulmonary embolism and deep vein thrombosis, one portal vein thrombosis). VTE was diagnosed already upon admission in 14 (34.1%) patients and 27 (65.9%) during hospital stay (18 in ICU and nine in wards outside the ICU). Multivariate analysis revealed D-dimer value > 3, 120   ng / ml (P < 0.001 ; OR 15.8, 95% CI 4.7-52.9) and duration of 8 days or more from COVID-19 symptoms onset to presentation (P 0.020; OR 4.8, 95% CI 1.3-18.3) to be independently associated with VTE upon admission. D-dimer value ≥ 3, 000   ng / l combined with a Wells score for PE ≥ 2 was highly specific (sensitivity 57.1%, specificity 91.6%) in detecting VTE upon admission. Development of VTE during hospitalization was independently associated with D-dimer value > 5, 611   ng / ml (P < 0.001 ; OR 6.3, 95% CI 2.4-16.2) and mechanical ventilation (P < 0.001 ; OR 5.9, 95% CI 2.3-15.1). Conclusions . VTE seems to be a common COVID-19 complication upon admission and during hospitalization, especially in ICU. The combination of Wells ≥ 2 score and D − dimer ≥ 3, 000   ng / l is a good predictor of VTE at admission.